2019
DOI: 10.1002/elsc.201900106
|View full text |Cite
|
Sign up to set email alerts
|

In sito galanthamine extraction during the cultivation of Leucojum aestivum L. shoot culture in two‐phase bubble column cultivation system

Abstract: Two‐phase bioreactor cultivation system was developed and applied for in sito recovery of extracellular galanthamine during the cultivation of Leucojum aestivum L. shoot culture in a modified column bioreactor system. The inclusion of an external circulation column with adsorbent resin Amberlite XAD‐4 as a second phase, on the 21st day of the beginning of cultivation resulted in 1.25 folds increase in biomass accumulation and maximal amounts of accumulated galanthamine of 6 mg/L (3.1 mg/L intracellular and 2.9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…As stated in the Introduction, the optimization of the production process of Amaryllidaceae alkaloids is well documented, especially in the case of galanthamine [ 24 , 27 , 29 , 30 , 31 , 32 , 33 ]. It is clear that the main stages of such optimization are: optimization of the nutrient medium for maximal yields of the target alkaloids; selecting the appropriate cultivation system and improving its design; optimization of the environmental conditions of cultivation and process control, management and modeling.…”
Section: Biotechnological Production Of Amaryllidaceae Alkaloidsmentioning
confidence: 99%
See 3 more Smart Citations
“…As stated in the Introduction, the optimization of the production process of Amaryllidaceae alkaloids is well documented, especially in the case of galanthamine [ 24 , 27 , 29 , 30 , 31 , 32 , 33 ]. It is clear that the main stages of such optimization are: optimization of the nutrient medium for maximal yields of the target alkaloids; selecting the appropriate cultivation system and improving its design; optimization of the environmental conditions of cultivation and process control, management and modeling.…”
Section: Biotechnological Production Of Amaryllidaceae Alkaloidsmentioning
confidence: 99%
“…Results received from this experimental work revealed that more than 40% of alkaloids were secreted into the culture liquid [ 24 ] and this required further improvement of the design of the cultivation system to a two-phase bioreactor cultivation system. An essential part of this cultivation system was an external circulation column filled with adsorbent resin [ 33 ]. Using this system for the cultivation of L. aestivum shoots, metabolism of Amaryllidaceae alkaloids was redirected preliminary to galanthamine synthesis.…”
Section: Biotechnological Production Of Amaryllidaceae Alkaloidsmentioning
confidence: 99%
See 2 more Smart Citations
“…Leucojum aestivum L., popularly known as summer snowflake, is an example of valuable plants which, despite its extremely high industrial potential, has received little attention regarding its protection and propagation (Kohut et al, 2007). During the past three decades, many natural L. aestivum habitats have fallen under threat due to the increasing demand by the pharmaceutical companies (Ivanov et al, 2019), while Ekıcı (2017) claimed that this plant species has the potential for an alternative tourism type, i.e. flora tourism, due to its visual impacts on the landscape.…”
Section: Introductionmentioning
confidence: 99%